2005
DOI: 10.1103/physrevlett.95.268301
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Flow of Soft Glasses by Soft Additives

Abstract: We examine the vitrification and melting of asymmetric star polymer mixtures by combining rheological measurements with mode coupling theory. We identify two types of glassy states, a single glass, in which the small component is fluid in the glassy matrix of the big one, and a double glass, in which both components are vitrified. Addition of small-star polymers leads to melting of both glasses, and the melting curve has a nonmonotonic dependence on the star-star size ratio. The phenomenon opens new ways for e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
101
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 27 publications
10
101
0
Order By: Relevance
“…A common method to induce this effective attraction in melts of star polymers would be through depletion interaction mediated by suitable additives. 13 Definitely this is not the cause of the attractive interaction in our case since our synthesis procedure ensures removal of all residual free PST chains. Probably the attraction arises due to dispersion forces.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…A common method to induce this effective attraction in melts of star polymers would be through depletion interaction mediated by suitable additives. 13 Definitely this is not the cause of the attractive interaction in our case since our synthesis procedure ensures removal of all residual free PST chains. Probably the attraction arises due to dispersion forces.…”
mentioning
confidence: 89%
“…9,10 Accordingly, it has been predicted 11,12 that star polymers with f Յ 30 show fluidlike behavior at all volume fractions, while for f Ͼ 30, various ordered phases as well as vitrification is expected to take place and to be observed experimentally, 4,13 as a function of volume fraction or packing density . However, recently it has been shown that superposition of an attractive interaction on the soft repulsive interaction leads to significant alteration of the phase diagram.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The simplest model are binary hard-sphere mixtures with large size disparity, where experiments on colloidal suspensions indeed found, depending on relative concentration, a partially frozen "single glass" with mobile small particles, separate from a "double glass" where both particle species freeze [10,11]. In mixtures of star polymers [12][13][14] yet another kind of glass emerged, termed "asymmetric" because it is characterized by few big particles frozen in a small-particle matrix, rendering the big-particle nearestneighbor cages highly nonspherical. It was, however, argued to be a hallmark of the ultra-soft interactions typical for the star polymers.…”
Section: Pacs Numbers: Pacs Tbdmentioning
confidence: 99%
“…Therefore, star polymers feature tunable softness, which is responsible for the observation of anomalous structural behavior [9] and for the formation of several crystal structures [5,10]. Mixtures of soft particles offer a much higher versatility with respect to their hard counterparts, both in terms of structural and rheological properties [11][12][13] and of effective interactions [14]. In particular, mixtures of star polymers of different sizes and functionalities have been recently investigated in a joint theoretical and experimental effort, revealing the existence of multiple glassy states [15].…”
mentioning
confidence: 99%